An Assessment on Average Pressure Drop and Dust-Holding Capacity of Hollow-Fiber Membranes in Air Filtration - Pavel Bulejko; Ondřej Krištof; Miroslav Dohnal (Membranes, 2021)
In this work, we tried to analyze dust loading behavior of polypropylene hollow fiber membranes using average pressure drop models. Hollow fiber membranes varying in fiber diameter were loaded with a standardized test dust to simulate particle-polluted air. We measured pressure drop development of the membranes at different flowrates and dust concentrations, and, after each experiment, the dust deposited on the membrane fibers was weighed to obtain dust holding capacity (DHC). The obtained experimental data was analyzed using various average pressure drop models and compared with average pressure drop obtained from pressure drop/dust load dependence using a curve fit. Exponential and polynomial fitting was used and compared. Pressure drop in relation to the dust load followed different trends depending on the experimental conditions and inner fiber diameter. At higher flowrate, the dependence was polynomial no matter what the fiber diameter. However, with higher fiber diameter at lower permeate velocities, the dependence was close to exponential curve and followed similar trends as observed in planar filter media. Dust-holding capacity of the membranes depended on the experimental conditions and was up to 21.4 g. However, higher dust holding capacity was impossible to reach no matter the experiment duration due to self-cleaning ability of the tested membranes.